PSYCHOLOGICAL CONDITIONS AFFECTING INTERNET ADDICTION IN ADOLESCENTS (Universal International Scientific Journal, 2026)
This article analyzes the psychological states that influence excessive Internet use and the formation of Internet addiction in adolescence. As a result of the widespread use of Internet technologies, cases of excessive dependence on the virtual environment are increasing among young people. Adolescence is a psychologically sensitive period, during which emotional instability, self-awareness processes, and the need for social relationships increase. Therefore, some psychological factors - a sense of loneliness, anxiety, depressive states, low self-esteem, and stress - appear as important factors in the formation of Internet addiction. The article discusses the relationship of these psychological states with Internet use behavior based on scientific sources.
Keywords: Internet addiction, adolescent psychology, psychoemotional state, anxiety, depression, social adaptation, virtual environment